SMART VILLAGE ECOSYSTEMS: INTEGRATING IOT, FINTECH, AND DIGITAL LITERACY TO BOOST INCLUSIVE RURAL DEVELOPMENT - Indah Sari, Ani (Journal of Economic Development and Village Building, 2025)
Rural communities face mounting development challenges, including poverty, limited access to infrastructure, and economic marginalization. At the same time, technological advances offer potential solutions through innovative village ecosystems integrating the Internet of Things (IoT), financial technology (fintech), and digital literacy initiatives. This research investigates how smart village ecosystems integrating IoT, fintech, and digital literacy can advance inclusive rural development, examining technology adoption patterns, digital capability development, financial inclusion mechanisms, and the factors that enable or constrain equitable participation. The study employed a qualitative exploratory case study design across two contrasting villages in the Cirebon district, West Java, Indonesia. Results reveal stark disparities between villages with advanced versus minimal ecosystem development. Setuapok village demonstrated functional IoT integration (agricultural sensors, village information systems, innovative governance platforms), diverse fintech adoption (mobile banking, digital payments, agricultural lending platforms), and systematic digital literacy programming reaching 68% of adults. In contrast, Karangsuwung village showed minimal IoT deployment, limited fintech access, and only 23% digital literacy coverage. However, even in the advanced village, inclusion remained highly uneven: while educated middle-aged males achieved comprehensive access to technology and benefits, marginalized groups faced persistent barriers. Women encountered gender-based constraints (cultural norms restricting mobility and technology use, domestic responsibilities limiting participation time, and male-dominated training environments). Elderly residents faced age-based exclusion (digital illiteracy, physical/cognitive limitations using interfaces, technology designs ignoring accessibility needs). Poor households experienced socioeconomic barriers (inability to afford devices, limited education constraining learning, livelihood pressures preventing training attendance).